Dinámica de crecimiento de especies leñosas del páramo andino del “Parque Universitario Francisco Vivar Castro” - Torres Acaro, Bryan Fabricio (2025)
Planning the use of resources to ensure the conservation of woody plant species is essential to understand the dynamics of an ecosystem, which involves knowing the behavior of variables such as growth. The study was conducted in the anthropogenic high mountains of the Francisco Vivar Castro University Park, with the aim of determining the growth of woody species in this ground over a seven-year period, through which ecological groups of woody species were identified in the park. Ten permanent plots of 25 m2, established in 2017, were measured, where the basal diameter (DAB) and the total height of woody individuals were recorded, along with the measurement of newly recruited individuals. The growth and periodic increase of DAB and height were calculated. A total of 1,205 individuals were recorded, of which 135 were new recruits by 2024, distributed across 8 families, 13 species, and 12 genera. The mortality rate was 4.55%, while the recruitment rate was 1.69%, resulting in a total dynamism of 3.12%. The average basal diameter growth was 1.77 ± 0.52 mm, while the height growth was 0.19 ± 0.05 m. Tibouchina laxa exhibited the greatest increase in basal diameter, whereas Clinopodium taxifolium showed the highest growth in total height. In contrast, the species with the lowest growth in basal diameter were Dendrophorbium scytophyllum and Brachyotum campanulare, while those with the lowest height growth were Gaultheria reticulata and Myrsine andina. The ecological groups of woody species, based on basal diameter and height, were divided into two well-defined groups, identifying species with higher and lower growth rates.